2020
DOI: 10.7150/jca.46383
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implication and functional annotations of APOBEC3G expression in patients with Melanoma

Abstract: Aim: Skin cutaneous melanoma (SKCM) is one of the most life-threatening malignancies damaging human health. APOBEC3G (A3G) has been found in several cancers; however, the role of A3G in SKCM is rarely studied. This study aimed to investigate the expression of A3G in tumor tissue and its prognostic value in SKCM patients. Method: A total of 512 SKCM patients from the First Affiliated Hospital of Soochow University (FAHSU) and the Cancer Genome Atlas (TCGA) database were consecutively recruited in analyses. Diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…APOBEC3G gene and protein expression was significantly more abundant in melanoma compared to adjacent normal tissues, and its higher expression was associated with longer overall and recurrence‐free survival. Moreover, APOBEC3G expression is positively correlated with the infiltration of B cells, CD8+ T cells, macrophages, neutrophils, and dendritic cells 32 . Our present results warrant further analyses regarding the role of APOBEC3G in bladder cancer, which may be methodologically hampered due to challenging immunological differentiation between various members of the APOBEC family 33 …”
Section: Discussionmentioning
confidence: 58%
“…APOBEC3G gene and protein expression was significantly more abundant in melanoma compared to adjacent normal tissues, and its higher expression was associated with longer overall and recurrence‐free survival. Moreover, APOBEC3G expression is positively correlated with the infiltration of B cells, CD8+ T cells, macrophages, neutrophils, and dendritic cells 32 . Our present results warrant further analyses regarding the role of APOBEC3G in bladder cancer, which may be methodologically hampered due to challenging immunological differentiation between various members of the APOBEC family 33 …”
Section: Discussionmentioning
confidence: 58%
“…It is reported that GBP2 exerted anti-tumour effects by inhibiting the Wnt/b-catenin pathway in skin cutaneous melanoma (SKCM) (57) and showed an association with poor prognosis in SKCM when its expression decreased (58). APOBEC3G, as a member of the cellular polynucleotide cytidine deaminases, catalyzes the deamination of cytosine to uracil in single-stranded DNA (59, 60) is significantly correlated with better prognosis when its expression is elevated in SKCM patients (61). As for THBS4, its potential role and prognostic performance in melanoma remains unclear but it is linked to poor prognosis in many other cancers: it effects the amplification and metastasis of gastric cancer positively (62); it may facilitate invasion of tumour cells in breast cancer (63); it accelerates HCC progression by modulating ITGB1 through FAK/PI3K/AKT pathway (64).…”
Section: Discussionmentioning
confidence: 99%
“…APOBEC3G affected the prognosis of patients by regulating tumor cell proliferation and innate immune response. It is expected to be a potential prognostic marker and an immunotherapy target [32][33][34]. APOBEC3G can affect DNA activity.…”
Section: Discussionmentioning
confidence: 99%